Determining Constructions Phase Risk Mitigation of Shutdown Valve Control Panel Replacement Project West Madura Offshore - Shoffan Abdi Tunggal; Ervina Ahyudanari (Institut Teknologi Sepuluh Nopember, 2020)
PHA is an oil and gas Cooperation Contract Contractor (KKKS) in Indonesia, playing an important role in achieving the national oil and gas production target. To maintain operational and production continuity, a replacements shutdown valve control panel project performs at the production facility of West Madura offshore field. It was the first control panel replacement project carried out at the live production facility. Project team identify some high risk activity through process and occupational safety. Research needs in order to determine construction phase project risk mitigation, by hazard identification, risk analysis, classification and proposed preventive actions as necessary. Proposed analysis and risk management determined by Focus Group Discussion and House of Risk modeling methods, research identified 23 risk events, 23 risk agents, risk mitigation defined by aggregate risk potential and its prioritie. Aiming on reducing risk occurrence and improving positive impact for sustainability and objectives of the project. 24 preventive actions are selected with 5 top priority preventive action proposed.